Occupational Mobility in Europe: Extent, Determinants and Consequences - Ronald Bachmann; Peggy Bechara; Christina Vonnahme (Institute of Labor Economics (IZA), 2019)
We examine occupational mobility and its link to wage mobility across a large number of EU countries using worker-level micro data. In doing so, we document the extent, the individual-level determinants and the consequences of occupational mobility in terms of wage outcomes and structural change across the EU. In addition, we identify potential explanations for the observed cross-country variation. Our results show that on average, 3% of European workers change their occupation per year, and that the extent of occupational mobility differs strongly by country. Individual characteristics play an important role for person-specific occupational mobility, but have little explanatory power for differences between countries. Occupational mobility is strongly associated with earnings mobility, and occupation movers are more likely than job movers to experience a downward rather than an upward earnings transition; by contrast, changing occupation voluntarily is more often followed by an upward wage transition. As opposed to composition effects, employment protection legislation seems to play an important role for explaining cross-country differences in occupational mobility through its impact on overall job mobility.
Keywords: J62; J63; P52; 330; occupational mobility; job mobility; wage mobility; European labour markets; EU-SILC